From Public Labs to Private Firms: Magnitude And Channels of Local R&D Spillovers - Antonin Bergeaud; Arthur Guillouzouic; Emeric Henry; Clément Malgouyres (The Quarterly Journal of Economics, 2025)
Abstract Introducing a new measure of scientific proximity between private firms and public research groups and exploiting a multibillion-euro financing program of academic clusters in France, we provide causal evidence of local spillovers from academic research to firms in the private sector. Our main estimate suggests that each €1 spent in academic research through this program spurred an additional €0.81 in private R&D expenditures. We also show that this shock increased the average quality of patents. We exploit reports produced by funded clusters, complemented by data on firm creation, labor mobility, and R&D public–private partnerships, to provide evidence on the channels for these spillovers. We discuss the policy implications of funding academic research to stimulate private R&D.